'A victim, and that's all': the construction of Meredith Kercher in the British national newspapers. Issue 7 (2nd October 2020) - Goulandris, Atalanta; McLaughlin, Eugene
ABSTRACT: What journalistic techniques are employed to construct a newsworthy female murder victim in the age of social media? Focusing on Meredith Kercher's murder, this article examines how Kercher's victim persona was fashioned by the British national press before the arrests of Amanda Knox and two others. Contrary to prevailing perspectives, we argue that the newsworthy murder victim is not necessarily an ideal victim. Murder victim status in a news story is a multi-faceted construction, contingent on whatever will magnify newsworthiness. The Kercher case is the first example of British journalists using the murder victim's Facebook content as the primary news resource, adding "authenticity" to the text and images used, since it originated from the victim herself. The research findings illustrate how Kercher was sexualized through the application of misogynist victim-blaming templates used in the reporting of sex crimes. It was the degradation of her ideal victim status that drove the initial newsworthiness of the murder story.